Elastography techniques in the evaluation of deep vein thrombosis - Hoang, Peter; Wallace, Alex; Sugi, Mark; Fleck, Andrew; Pershad, Yash; Dahiya, Nirvikar; Albadawi, Hassan; Knuttinen, Grace; Naidu, Sailendra; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
Abstract: Deep venous thrombosis (DVT) is a significant medical problem with an incidence of 1 in 1,000 adults and greatly reduces quality of life through post-thrombotic syndrome. Treatment choice for DVT can be influenced by the age of the clot. While new endovascular catheter techniques treat venous clots to potentially prevent post-thrombotic syndrome, they require improved imaging techniques to accurately determine clot age. This review investigates experimental and clinical evidence of elastography techniques for aging DVT. Strain elastography and shear wave elastography are the most common techniques to age thrombus. These elastography techniques can distinguish between acute and chronic clots by characterizing tissue stiffness. When clot age cannot be determined with ultrasound duplex analysis, elastography may offer a helpful adjunct. However, further investigation is required to validate accuracy and reproducibility for clinical implementation of this novel technique.